Perubahan Penggunaan Lahan dan Tutupan Lahan Menggunakan Metode Maximum Likelihood - Amniar Ati; Septianto Aldiansyah; Hasni Hasan; Windayani Windayani; Harmiaty Bahar; Muhammad Saleh Qadri; Abdi Juryan Ladiando; Ade Putra (Jurnal Penelitian Pendidikan Geografi, 2025)
Changes in land use and cover are inevitable as a result of human intervention, both cyclically and permanently. Rapid population growth accompanied by increasing demand for land, often results in conflicts of interest over land, resulting in inconsistencies between land use and spatial planning. The purpose of this study is to determine changes and land use from 2014 to 2023. The classification method used in this study is Maximum Likelihood. The data in this study were processed from Landsat 8 OLI/TIRS Satellite Imagery for 2014 and Landsat 9 OLI-2/TIRS-2 for 2023. The results of the study showed that built-up land and open land increased by 6.89 km2 and 9.27 km2 respectively. Meanwhile, agriculture and vegetation tended to decrease by 12.11 km2 and 4 km2 respectively. These results sufficiently describe the conditions of changes in land use and cover that occurred in Lasalimu District, considering that the accuracy of the resulting map is >80%.